FENOMENA TIPOLOGI GRAMATIKAL BAHASA MINANGKABAU: AKUSATIF, ERGATIF, ATAU CAMPUR? - Jufrizal Jufrizal (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2009)
The typological dichotomy of grammatical structures of languages in the world as accusative and ergative languages gets “challenged” from linguistics data of Minangkabaunese. There are types of grammatical structures of clauses in this local language which has grammatical properties as accusative constructions and others are ergative ones. The ideas of split-S and fluid-S become other typological analyses that could be used to learn the grammatical properties of Minangkabaunese. Another grouping of languages which needs further proof is that the ‘mixed’ or ’neutral’ languages. This paper discusses the syntactical phenomena of Minangkabaunese as a ‘mixed’or ’neutral’ language based on grammatical typology theoretical framework.